2011
DOI: 10.1007/s00134-011-2445-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes in survivors of acute respiratory distress syndrome ventilated in supine or prone position

Abstract: No differences in pulmonary function or quality of life were observed in this small group of ARDS survivor patients treated in prone versus supine position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 50 publications
2
33
1
2
Order By: Relevance
“…To investigate the influence of rescue therapies on 1-y mortality, Chiumello et al 25 compared ARDS subjects ventilated in prone or supine position without finding any difference, although they reported an overall high mortality rate (60%). They could not establish whether this high rate was mainly due to respiratory function impairment or extrapulmonary complications.…”
Section: Long-term Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the influence of rescue therapies on 1-y mortality, Chiumello et al 25 compared ARDS subjects ventilated in prone or supine position without finding any difference, although they reported an overall high mortality rate (60%). They could not establish whether this high rate was mainly due to respiratory function impairment or extrapulmonary complications.…”
Section: Long-term Mortalitymentioning
confidence: 99%
“…56 Chiumello et al 25 investigated a group of ARDS subjects managed with protective ventilation previously enrolled in a randomized multi-center trial to test the long-term outcomes of patients receiving prone compared with supine positioning. The mean extent of reticular pattern was Ͻ10 -15% of total lung volume 1 y after ARDS in both supine and prone groups, and there were also no differences in the amount of collapsed (8.1 Ϯ 3.1% vs 7.3 Ϯ 3.4%), poorly aerated (15.3 Ϯ 3.6% vs 17.1 Ϯ 4.9%), and well aerated (64.0 Ϯ 8.4% vs 70.2 Ϯ 8.4%) tissue between the 2 groups.…”
Section: Radiological Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings reported by Needham and colleagues 4 were similar to a recent smaller European study where overall mortality in patients with ARDS at 12 months was 60%. 10 The study by Needham and colleagues 4 underscores the previous findings that LPV has not yet been applied systematically to patients with ARDS, even at centers with a high degree of experience with LPV. 11 Moreover, there is mounting evidence regarding the importance of limiting V T to prevent ARDS in at-risk patients, 12 as well as preventing both ARDS and non-pulmonary organ damage in patients without known risk factors.…”
Section: Tidal Volume and 2-year Mortality In Ardsmentioning
confidence: 92%
“…The full impact of ARDS extends beyond the fact of whether or not patients leave the hospital alive. Within the last few years, several studies have shown that long-term morbidity induced by ARDS is substantial, as patients may suffer from persistent physical constraints and weakness to new-onset neurocognitive disorders, such as depression and long-lasting cognitive impairment [2,3,10,11]. Among the major comorbidities, malignant disease has a major physical and psychological burden in itself [12].…”
mentioning
confidence: 99%